Interprofessional Academic Patient Aligned Care Team Panel Management Model - Gardner, Annette L. (Fed Pract, 2019)
The panel management model brings together trainees, faculty, and clinic staff to proactively provide team-based care to high-risk patients with unmet chronic care needs.